Human Relationship Management to Enhance Organizational Performance through Effective Communication and Team Collaboration - Sarimah; Fauziah Hayati Fazrin; Tisatun; Efrita Norman (MES Bogor, 2024)
The research explores the role of Human Relationship Management (HRM) in enhancing organizational performance through effective communication and team collaboration. This study aims to provide a comprehensive understanding of how structured communication and well-managed collaboration can positively impact productivity and project completion. The methodology used is a Systematic Literature Review (SLR), analyzing relevant studies from 2019 to 2024. The results indicate that structured communication increases organizational productivity by 30%, while effective team collaboration accelerates project completion by 20%. Additionally, HRM implementation can reduce internal conflicts by 15%, contributing to improved efficiency. The major conclusion is that HRM significantly enhances organizational performance by fostering a productive and harmonious work environment. This study contributes to the field by offering practical guidelines for organizations to adopt HRM strategies that emphasize communication and collaboration. The findings also provide a solid theoretical foundation, aligning with established theories on social interaction, team collaboration, and conflict management. The study's limitation lies in its reliance on existing literature from a limited timeframe, suggesting the need for further empirical testing across various organizational contexts.